SYSTEMATIC LITERATURE: TANTANGAN DAN INOVASI MANAJEMEN DALAM MENGELOLA PASAR MONOPOLI DI ERA GLOBAL - Arafah, Zahid Nugrah; AZ, Bambang; Al Faisal, Aldi; Zefriyenni, Zefriyenni (Komunitas Manajemen Kompetitif, 2025)
This study presents a Systematic Literature Review (SLR) on challenges and innovations in managing monopoly markets in the global era. The research collected articles published between 2015 and 2025 from Scopus, Web of Science, Dimensions, and Google Scholar following PRISMA guidelines. Through a rigorous selection process, eleven relevant articles were selected for further analysis. The findings reveal that monopoly markets in the digital era face complex challenges in the form of tension between innovation needs and antitrust regulations, where overly strict antitrust policies potentially hinder innovation incentives for dominant companies. The development of digital platform economies further complicates this dynamic through the formation of